Students' Difficulties In Arabic: A Study Of The Background Of Students Arabic Language Education - Norlaila, Norlaila; Muradi, Ahmad; Oensyar, M. Kamil Ramma; Arifin, Ahmad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This paper explores the difficulties in learning Arabic based on the students' backgrounds, along with various solutions that can maximize the effectiveness of Arabic Language Education for students. This research conveys a descriptive approach with a field study. It is a simple quantitative and qualitative descriptive study, providing a narrative description of the situation. Data was collected through interviews with 25 Arabic Program (PBA) students, PBA lecturers, and The Arabic Language Student Association (HMP PBA) activists. The data analysis model used in this research follows the model of Miles, Huberman, and Saldana. The result shows that each student in the PBA study program faces difficulties in Arabic language skills and components according to their educational background. Students from modern pesantren backgrounds do not experience many language difficulties. The most significant difficulty for students is kalam skills. The factors influencing language difficulties include interest, educational background, teaching and methodological aspects, environment, student activities, and psychological and economic factors. The efforts made by the study program to strengthen students' language skills are still limited, consisting mainly of additional activities such as kalam and qiraah practice. HMP Bahasa Arab also organizes language communities, such as language workshops (daurah lughah) and competitions related to Arabic language proficiency. However, these activities are only attended by some students who are already relatively proficient in the language.